Nursing practices regarding attention to women in situation of abortion - Maria Cidney da Silva Soares; Valéria Évila de Oliveira Freitas; Ana Rita Ribeiro Cunha; Jank Landy Simôa Almeida; Cláudia Maria Ramos Medeiros Souto; Rosane Arruda Dantas (Universidade Federal do Ceará, 2012)
This study aimed to investigate aspects that guide the nursing practices turned to women in abortion situation. Thereby, it was drawn a descriptive, exploratory study with qualitative approach developed in a public maternity in the city of Campina Grande - PB with 10 nursing team professionals who assisted women in abortion situation at the moment of the data collection. The data were analyzed according to thematic categorical analysis. We followed the ethical requirements laid out in Resolution 196/96 which involves research on human beings. The results evidenced two categories: technical perception of the care and care as a solidary bond, not as a human right. Therefore, it is concluded that the nurses' look at the woman in abortion situation is still discriminatory and purely technical and when it is evaluated in the perspective of humanization it is seen as care like solidary bond and not as human right.